The Role of Agricultural Extension on The Development of Farmers Group (Case Study: Pare Sub-district, Blitar Regency, East Java) - Ika Agustin Maulidiah; Gunawan Prayitno; Aris Subagiyo (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2021)
Agricultural extension is a learning process that designed to improve the skills of agricultural operators, in particular farmers. This study aimed to determine whether agricultural extension activities have a role to play in the development of Agro-politan areas and what factors impact agricultural extension. Descriptive statistical analysis, correlation analysis, and factor analysis were used. Based on descriptive statistical analysis, it can be seen that agricultural extension agents play a role in three subsystems in the Agropolitan Area (input subsystem, process subsystem, and marketing subsystem). Based on the correlation analysis and factor analysis, three factors influenced agricultural extension's success, such as the participation of farmers, the performance of agricultural extensions, and the methods of the extension used.